PRINSIP-PRINSIP KOMUNIKASI ISLAM: PERSPEKTIF HADIS NABI - Sunaryanto (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
There is a distinction between Western communication and Islamic communication, especially in terms of definition. In addition, Western communication is theoretically generated based on empirical observations. Islamic communication, apart from being based on empirical studies, cannot be separated from the Al-Qur'an and Hadis. Writing this paper aims to find out some of Isla communication ethics in the hadis. The method used is only using a library research approach. Data is only collected from the hadith books, books, journals, and several other studies. The conclusion in this paper is that there are many principles of Islamic communication in the hadis, for example the principle of honesty, the principle of effective speaking and others.